Rapid Screening: Post Computerized Tomography Incidence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Features in Asymptomatic Patients - Syed Muhammad Faiq; Syeda Nuzhat Zehra; Jafri , Syeda Sukaina, Sumreen Begum (International Journal of Endorsing Health Science Research, 2022)
Background: It is to document the frequency of incidental Corona Virus Disease-2019 (COVID-19) specific findings in patients imaged after the initial ten days of lockdown relief and the sensitivity of computed tomography (CT) in picking unknown ongoing disease processes. Case presentations: In this study, we presented seven cases—three cases in plain CT pyelogram and four cases of post-contrast scans. Post-contrast scans of chest findings in case 1 showed few pre-vascular, pre-tracheal, and sub-carinal lymph nodes with calcified granuloma in the left lower zone accompanied by extensive bilateral peripheral Ground Glass Haze with alveolar opacification. In Case 2, multiple non-homogeneous areas of ground-glass haze diffusely involving both lung fields were seen. Case 3 showed a few sub-centimeters mediastinal lymph nodes with diffuse mosaic attenuation patterns in both lung fields along with multiple soft tissues density nodules in both lungs. While in Case 4, Patchy areas of alveolar opacification with surrounding ground-glass haze were noted in lower lobes. Management and Results: Total 64 CT C/A/P (chest/abdomen/pelvis) with contrast scans and 120 plain pyelograms were done within ten days after lockdown relief, and it was observed that during the stricken lockdown, no incidental case of positive CT finding was observed. However, afterward, within this time, 44 cases (23.9%) were recorded in asymptomatic patients of COVID-19. Conclusions: CT chest is highly sensitive in detecting COVID-19 with high accuracy of featuring progress in the disease and associated findings even in the initial stages.